Ubiquitylation and proteasomal degradation of the p21(Cip1), p27(Kip1) and p57(Kip2) CDK inhibitors - Lu, Zhimin (2010)
The expression levels of the p21(Cip1) family CDK inhibitors (CKIs), p21(Cip1), p27(Kip1) and p57(Kip2), play a pivotal role in the precise regulation of cyclin-dependent kinase (CDK) activity, which is instrumental to proper cell cycle progression. The stabilities of p21(Cip1), p27(Kip1) and p57(Kip2) are all tightly and differentially regulated by ubiquitylation and proteasome-mediated degradation during various stages of the cell cycle, either in steady state or in response to extracellular stimuli, which often elicit site-specific phosphorylation of CKIs triggering their degradation.